HUBUNGAN PENDAPATAN USAHATANI DENGAN TINGKAT MIGRASI TENAGA KERJA MASYARAKAT PEDESAAN (KASUS DI DESA AYAH, KECAMATAN AYAH, KEBUMEN) - , AGAM RAFSANJANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Agriculture is the main occupation for Ayah Villageâs communities.Uniquely, in this village was found numbers of migration phenomenon especially international migration. This problem indicates to one big question: does agriculture sector canât give the communities some precious things to bring them to the bright future so they choose to migrate? The objective of this study is to explore the correlation between agricultural income with migration rate of rural manpower. This study uses survey method. Study area was chosen purposively in case Ayah Villageâs communities was dominated by worker that come from agricultural sector and also in this area was found numbers of migration phenomenon. Data aquistition was done by structural interrogation by using questionaire. The object was chosen purposively by some criteria which are farmer and have minimum one of migrating household member. Data analysis was conduct by using descriptive quantitative and statistical analysis. The result of this study shows that agricultural income is commonly low with income average about Rp1.198.000/month. Migration rate also shows small degree that shows <50% high. Correlation analysis shows that there is a weak correlation between agricultural income with the migration rate. The significance number is >0,05. It indicates that agricultural income and migration not really correlate each other.